Implementasi Program Subsidi Bunga Pinjaman Bagi Usaha Mikro Di Kota Pekanbaru - Widya Monica Lastri Pakpahan; Febri Yuliani (STISIPOL Raja Haji, 2026)
To support micro-business sector, the Pekanbaru City Government launched the 100% Loan Interest Subsidy Programme through City Regulation No. 13 of 2024, administered by PT. BPR Pekanbaru Madani. However, the implementation of the programme continues to face various challenges, marked by a low rate of fund disbursement, a decline in applications from 960 files (2024) to 460 files (2025), a high rate of file rejections, and delays in disbursement. This study aims to analyse the implementation of the Loan Interest Subsidy Programme for micro-enterprises in Pekanbaru City and to identify the factors hindering it. The study employed a qualitative method with a descriptive approach. Data were collected through interviews, observation and documentation, and were subsequently analysed using the Miles, Huberman and Saldana model. The research findings indicate that the programme’s implementation has proceeded reasonably well, but has not yet been optimal according to George Edward III’s indicators, namely communication, resources, disposition and bureaucratic structure. The challenges faced include uneven dissemination of information, limited human resources among implementing agencies, a low level of understanding of administrative requirements, a lack of Business Identification Numbers (NIBs), failure to pass the BI Checking, and the length of the verification and disbursement processes. This situation has led to many applications failing to meet the requirements and a low take-up rate of the subsidies. Consequently, there is a need to step up public awareness campaigns, provide administrative support and improve coordination amongst implementing bodies so that the programme can reach more micro-enterprises and achieve its stated objectives.